Pequeñas esculturas cristianas en madera policromada de la Frontera mapuche (Chile, siglos XVIII-XIX): El ejemplo de la Virgen del Boldo - Josefina Schenke (Nuevo mundo - Mundos Nuevos)
Many objects within Chilean museums remain unstudied. This is the case of some polychrome wooden sculptures whose origin cannot be traced back to foreign or Chiloé workshops stands out. The coherence of their morphological patterns and their conservation in a geographical area that coincides with the former territories of the Mapuche frontier seem to demonstrate that, from the second half of the 18th century onwards, a large amount of imagery may have been produced in that remote southern border of the Hispanic Monarchy. Art historiography has ignored these crude and simple pieces, usually describing them as mere expressions of "popular art" because they deviate from the naturalistic patterns set by the tradition of Spanish, Lima and Quito sculpture. In this article I shall consider one of these sculptures, the Virgen del Boldo, (Museo de Arte Religioso del Arzobispado de Concepción) in relation to the legend of the miraculous apparition of the Virgin Mary on a tree during a battle between Spaniards and Mapuche in Penco. This small sculpture summarizes the importance of this territory of “La Frontera” as a producer of a miraculous narrative with the impact of the Franciscan order. This narrative was embodied in a first image (probably from Quito) and that, through a process of symbolic appropriation, is again embodied in other images that obey a local manufacture.